Pengungkapan Model Mediasi Kepada Pihak Bersengketa Oleh Mediator Sebagai Pelaksanaan Prinsip Informed Consent (Kajian Mediasi Sektor Perbankan) - Harnowo, Tri; Shahab, Fahmi (UI Scholars Hub, 2024)
The mediation techniques commonly used by mediators are facilitative, evaluative, or hybrid models. The choice of mediation model generally depends on the complexity of the dispute, the nature of the relationship, and the expectations for further cooperation. This research examines the application and disclosure of mediation models in the banking sector. The methodology used is normative, analyzing regulations related to the application and disclosure of mediation models in the banking sector. Data collection was obtained from primary legal materials in the form of legislation, secondary legal materials such as professional codes of ethics, books, articles, and scientific journals, and tertiary legal materials such as dictionaries and encyclopedias. The researcher also used questionnaires and interview techniques to obtain data on the application of mediation models in the banking sector. The research results indicate that, from a conceptual aspect, the disclosure of mediation models to disputing parties by the mediator constitutes the implementation of the principle of informed consent. From a practical aspect, the disclosure of mediation models is important for disputing parties in the banking sector as it can help them prepare strategies to be taken, assess the suitability with their needs and objectives, manage expectations about what can be achieved, and choose the appropriate mediator. Based on banking mediation regulations and standards, the mediation model that should be applied is facilitative. However, in practice, banking mediators use a combination of facilitative and evaluative models. The recommendations include the obligation to disclose the mediation model used, which can be incorporated into legislation and/or mediator codes of ethics.